Exploring Barriers of Diabetic Programs in Primary Health Cares in Bukittinggi; Health Worker’s Perspective - Amelia, Dona; Srywahyuni, Ade; Merianti, Liza; Pratama, Engla Rati (Universitas Malahayati, 2025)
ABSTRACT The incidence of Diabetes Mellitus in Indonesia continues to increase each year. Nearly 75% of individuals with diabetes remain undiagnosed, posing a high risk of complications, disabilities, and premature death. Diabetes programs implemented in Primary Health Cares are divided into two categories: integrated within the Non-Communicable Disease (NCD) control program and integrated within the Chronic Disease Management program (Prolanis). However, not all activities are fully realized, so it is necessary to identify the barriers to the implementation of diabetes programs in these health centers. This research aims to investigate and provide an in-depth understanding of the obstacles faced by healthcare workers involved in diabetes programs at Primary health cares. The study sample consisted of 13 individuals selected through purposive sampling techniques. Data collection employed semi-structured interviews, and data analysis utilized the Collaizi method. The research identified six themes as follows: the absence of a specific diabetes program, program interruption during the COVID pandemic, most program participants being elderly, inadequate capacity of exercise fields, a shortage of human resources, and the remote location of the health centers from the working area. Based on the findings of this research, it is expected that future primary health care will establish an integrated diabetes program and increase the number of healthcare workers involved in managing Diabetes to ensure the optimal implementation of the program. Keywords: Barriers, Diabetes programs, Primary Health Care